Challenges confronting construction information management - Adekunle, Peter; Aigabvboa, Clinton; Thwala, Wellington; Akinradewo, Opeoluwa; Oke, Ayodeji (Frontiers in Built Environment, 2022)
This paper intends to unveil the outcome of an appraisal of the prevailing challenges of construction information management. The study implemented a quantitative survey tactic with the aid of questionnaire as the mechanism for data gathering from architects, civil engineers, quantity surveyors, mechanical and electrical engineers, construction managers and project managers. Data analysis ensued with the aid of SPSS software package in which applicable measure of disperse and inferential statistics were implemented. The study unveils that information management is a major aspect of construction procedure and that to achieve in construction, there must be well-structured information system. Also, it was discovered that construction information management can be affected by both internal and external factor within an organization. Further findings revealed that long-term reliance on legacy system, lack of technological equipment, leadership development, poor financial investment on infrastructure for data management and management implementing appropriate policies are the major challenge of construction information management. The prowess of this study depends on the appraisal of the challenges of construction information management and how identification of the challenges can help to proffer solutions to improve methods of managing construction information for better performance and efficient service delivery within the construction industry.